1994
DOI: 10.3109/00365599409180482
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Thiosulphate in the Treatment of Renal Tubular Acidosis I with Nephrocalcinosis

Abstract: Nephrocalcinosis is a common feature in renal tubular acidosis I (RTA-I) and contributes to renal insufficiency. We describe a patient, 37 years old, with RTA-I, mild renal failure and extended nephrocalcinosis. His disease was diagnosed in age 28 and patient is under treatment with sodium bicarbonate, potassium gluconate and sodium thiosulphate for 9 years. By this treatment nephrocalcinosis and renal function have not been worsened and patient is without clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The only other report of STS therapy in kidney stone disease was a case report in 1994 of a patient with renal tubular acidosis and nephrocalcinosis, which improved with oral STS therapy. 32 No other studies either supporting or refuting the The mechanism by which thiosulfate reduces pathologic crystallization is not known. Yatzidis suggested that thiosulfate complexed calcium, because calcium thiosulfate is much more soluble than either CaOx or calcium phosphate; however, the solubility of a salt does not indicate the ability of a one molecule to complex another.…”
Section: Discussionmentioning
confidence: 99%
“…The only other report of STS therapy in kidney stone disease was a case report in 1994 of a patient with renal tubular acidosis and nephrocalcinosis, which improved with oral STS therapy. 32 No other studies either supporting or refuting the The mechanism by which thiosulfate reduces pathologic crystallization is not known. Yatzidis suggested that thiosulfate complexed calcium, because calcium thiosulfate is much more soluble than either CaOx or calcium phosphate; however, the solubility of a salt does not indicate the ability of a one molecule to complex another.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the patients had regression of the calcified mass as well as improved motility of the affected joints (20). STS was given for a period of 9 yr to a patient with nephrocalcinosis as a result of renal tubular acidosis type 1 (21). There was no further deterioration of his condition, and the discontinuation of the medication was accompanied by recurrence of renal colic.…”
Section: Discussionmentioning
confidence: 99%
“…He reported an 80% reduction in stone rates compared with the patients’ own pretreatment stone formation rate. Oral STS (a dose of 15–20 mmol per day) was used, along with potassium and alkali, to treat a young patient who presented with prolonged history of recurrent renal colic and passage of small kidney stones, due to type I renal tubular acidosis with bilateral nephrocalcinosis and stage III chronic kidney disease [21]. During the 9 years of therapy, the patient did not have any colic, did not develop side effects, and had stable nephrocalcinosis with slight improvement on creatinine clearance.…”
Section: Discussionmentioning
confidence: 99%